262 Brassicas as an alternative forage in the northeastern United States. (5th December 2019) - Billman, Eric D; Dillard, S Leanne; Soder, Kathy J
Abstract: In the northeastern United States, winter forage management has traditionally necessitated either: a) feeding conserved forages, or b) stockpiling grazeable perennial forage. Forage brassicas offer a low-cost alternative to these strategies. This project evaluated performance of different annual forage brassicas in northeastern forage production systems. Three brassicas, 'Barisca' rapeseed (Brassica napus L.), 'Inspiration' canola (B. napus L.), and 'Appin' turnip (B. rapa L.) were compared against 'KB Supreme' annual ryegrass (Lolium multiflorum Lam.) for dry matter yield and nutritive value over two autumn production seasons. Replicated plots were 5.5 × 9.1 m and seeded (brassicas at 5.6 kg/ha; ryegrass at 22.4 kg/ha) in August of 2015 and 2016 in a randomized complete block design. Four harvests occurred each year at two-week intervals following initial harvest. Statistical analyses were conducted using PROC GLIMMIX in SAS 9.4; harvest and species were fixed effects, while year and its interactions were considered random. Harvest date had no significant impact on DM yield (P > 0.05). All brassica yields (734 – 861 kg/ha) were significantly greater (P < 0.001) than annual ryegrass (344 kg/ha). This indicated brassica yield was superior under environmental stress conditions that hinder annual ryegrass growth. Nutritive value concentration suggested ryegrass had greater CP (28.1%) than the brassicas (24.2 – 25.4%) and minimal differences in net energy content (< 2%) among species (P < 0.001). However, per-area (kg/ha) values resulted in consistently greater (P < 0.001) CP (176 – 204 kg/ha), and NEL (1.2 – 1.5 Mcal/ha) than annual ryegrass (CP = 88 kg/ha; NEL = 0.56 Mcal/ha). Therefore, the greater yield potential of forage brassicas allows them to supply greater nutrient supplementation during periods of low forage availability, at a reduced feeding cost.